Effects of Using Virtual Laboratory Experiments on Students’ Achievement in Chemistry - Avwiri, Hannah E; Odiri, Onoshakpokaiye E. (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The study examined the effect of the use of Virtual Laboratory Experiments (VLE) on students’ achievement in chemistry. The study employed two hypotheses and two research questions. The design used was quasi-experimental, specifically the pretest-posttest non-equivalent control group one. The study's participants were 2,918 secondary school senior students in Delta, Nigeria. We selected 87 students from intact classes in two schools, using purposive and random selection methods. Three experts verified the data collected using the Chemistry Practical Achievement Test (CPAT). Using Kuder-Richardson Formula 20, we established the internal consistency and found a coefficient of 0.78. We used the mean, standard deviation, and analysis of covariance to analyze the study's data. Considering the research, students who were instructed in chemistry via VLE achieved better than those who trained applying DTI in relation to the mean scores of achievements. Additionally, there was a notable difference in the mean achievement score between students who were instructed in chemistry using the Demonstration Teaching Method (DTM) and those who were educated in chemistry using VLE. It was suggested that chemistry teachers receive regular training on how to incorporate contemporary technology into the instruction and learning of chemistry, particularly regarding the application of virtual chemistry laboratory experiments. This is because virtual learning environments (VLEs) may be utilized to guarantee that experiments are taught frequently and serve as a workaround for inadequate laboratory supplies and equipment.